ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND COMMUNICATION STYLES ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE MOTIVATION AT THE OFFICE OF PERUM BULOG DIVRE SOUTH SULAWESI - Nurdin Brasit; M. Sobarsyah; st, aisyah (Scientia integritas Utama, 2023)
Analysis of Transformational Leadership Style and Communication on Employee Performance through Employee Motivation (Study at the Office of the Regional Bureau of Logistics of the Regional Logistics Agency of South Sulawesi).(Supervised by Nurdin B Dan Syobarsyah). This study aims to analyze the influence of: 1) Transformational leadership style on employee motivation, 2) Communication on employee motivation, 3) Transformational leadership style on employee performance, 4) Communication on employee performance, 5) Employee motivation on employee performance. This research uses the method path analysis, using exogenous and endogenous variables. The results of this study indicate that: 1) Transformational leadership style has a direct, positive and significant effect on employee motivation, 2) Communication has a direct, positive and significant effect on employee motivation, 3)Transformational leadership style influences [(directly and indirectly (through employee motivation)], positively and significantly to employee performance,4)Communication has an indirect effect on employee performance and is not significant, 5)Employee motivation has a direct, positive and significant effect on employee performance.